Sanciones administrativas por contaminación ambiental de Ríos y vertientes, y la vulneración de los derechos constitucionales de la naturaleza. Quevedo - Ochoa Baquezea, Manuel Salvador (2015)
The present research on the theme: Administrative Sanctions for pollution of rivers and springs and the violation of the constitutional rights of nature. Therefore the main objective of this work is achieved through an amendment to Article 44 of the codification of the law of environmental management to protect the constitutional rights of free evil nature. This legal research is organized into six chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter the methodology used in the research described in point; methods applied, types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research findings obtained by interviewing